160k views
2 votes
PLEASE HELP, DUE AT MIDNIGHT >>>>>

PLEASE HELP, DUE AT MIDNIGHT >>>>>-example-1
User Bcumming
by
4.8k points

1 Answer

7 votes

Answer:

BELOW

Explanation:

7.


\mathrm{Slope}=(y_2-y_1)/(x_2-x_1)\\\\\left(x_1,\:y_1\right)=\left(-8,\:-11\right),\:\left(x_2,\:y_2\right)=\left(17,\:4\right)\\\\m=(4-\left(-11\right))/(17-\left(-8\right))\\\\m = (4+11)/(17+8)= (15)/(25) \\\mathrm{Refine}\\\\m=(3)/(5)

8.


\mathrm{Slope}=(y_2-y_1)/(x_2-x_1)\\\\\left(x_1,\:y_1\right)=\left(10,\:-15\right),\:\left(x_2,\:y_2\right)=\left(13,\:-17\right)\\\\m=(-17-\left(-15\right))/(13-10)\\\\m = (-17+15)/(13-10)\\ \\m = (-2)/(3)\\ \\Simplify\\m=-(2)/(3)

9.


\mathrm{Slope}=(y_2-y_1)/(x_2-x_1)\\\\\left(x_1,\:y_1\right)=\left(-6,\:-7\right),\:\left(x_2,\:y_2\right)=\left(5,\:-7\right)\\\\m=(-7-\left(-7\right))/(5-\left(-6\right))\\\\m = (-7+7)/(5+6)\\ \\m = (0)/(11)\\ \\Simplify\\m=0

10.


\mathrm{Slope}=(y_2-y_1)/(x_2-x_1)\\\\\left(x_1,\:y_1\right)=\left(-4,\:-3\right),\:\left(x_2,\:y_2\right)=\left(2,\:-9\right)\\\\m=(-9-\left(-3\right))/(2-\left(-4\right))\\\\m = (-9+3)/(2+4)\\ \\m = (-6)/(6) \\\\Simplify\\m =-1

11.


\mathrm{Slope}=(y_2-y_1)/(x_2-x_1)\\\\\mathrm{When\:}y_1\\e \:y_2\mathrm{\:and\:}\:x_1=x_2\mathrm{\:the\:slope\:is\:}\infty \\\\m = \infty

12.


\mathrm{Slope}=(y_2-y_1)/(x_2-x_1)\\\\\left(x_1,\:y_1\right)=\left(-5,\:3\right),\:\left(x_2,\:y_2\right)=\left(19,\:-6\right)\\\\m=(-6-3)/(19-\left(-5\right))\\\\m = (-6-3)/(19+5)\\ \\m = (-9)/(24)\\ \\Simplify\\m=-(3)/(8)

13.


\mathrm{Slope}=(y_2-y_1)/(x_2-x_1)\\\\\left(x_1,\:y_1\right)=\left(-7,\:-12\right),\:\left(x_2,\:y_2\right)=\left(1,\:-16\right)\\\\m=(-16-\left(-12\right))/(1-\left(-7\right))\\\\m = (-16+12)/(1+7) \\\\m = (-4)/(8) \\\\Simplify\\m=-(1)/(2)

14.


\mathrm{Slope}=(y_2-y_1)/(x_2-x_1)\\\\\left(x_1,\:y_1\right)=\left(-18,\:0\right),\:\left(x_2,\:y_2\right)=\left(-13,\:1\right)\\\\m=(1-0)/(-13-\left(-18\right))\\\\m = (1-0)/(-13+18)\\ \\m = (1)/(5) \\

15.


\mathrm{Slope}=(y_2-y_1)/(x_2-x_1)\\\\\left(x_1,\:y_1\right)=\left(1,\:-11\right),\:\left(x_2,\:y_2\right)=\left(-2,\:-4\right)\\\\m=(-4-\left(-11\right))/(-2-1)\\\\m = (-4+11)/(-2-1)\\ \\m = (7)/(-3) \\\\Simplify\\m=-(7)/(3)

User Sergei Volkov
by
5.3k points